2019
DOI: 10.32098/mltj.02.2013.03
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking and musculoskeletal disorders

Abstract: Cigarette smoking has deleterious effects on the musculo-skeletal system. The loss of bone mineral content and increased incidence of fractures are the best known negative consequences. The pathogenesis is complex, due to direct toxic effects on osteoblasts/osteoclasts activity of nicotine, and indirect actions on sex and adrenocortical hormones, vitamin D, intestinal calcium absorption, vessels and oxygen supply. Smoking may favour the onset or aggravate the progression of rheumatoid arthritis and back pain. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
2
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(75 citation statements)
references
References 45 publications
(53 reference statements)
2
69
2
2
Order By: Relevance
“…In such cases, there is a chaotic production of extra-cellular matrix by tenocytes and chaotic expansion of newly formed capillary vessels, and this results in decreased mechanical durability of the tendon and the clinical manifestation of its disorder. Smoking has a significant effect on the musculoskeletal system, which was presented by authors in the RCT and Achilles tendon studies; however, there are a lack of data about the effect of smoking on LHBT disorders, particularly at the microscopic level [7].…”
Section: Introductionmentioning
confidence: 99%
“…In such cases, there is a chaotic production of extra-cellular matrix by tenocytes and chaotic expansion of newly formed capillary vessels, and this results in decreased mechanical durability of the tendon and the clinical manifestation of its disorder. Smoking has a significant effect on the musculoskeletal system, which was presented by authors in the RCT and Achilles tendon studies; however, there are a lack of data about the effect of smoking on LHBT disorders, particularly at the microscopic level [7].…”
Section: Introductionmentioning
confidence: 99%
“…A Brinkman index greater than or equal to 400 identifies subjects as heavy smokers, and lower than 400 as moderate smokers 22 . Smokers with a Brinkman index greater than 400 had lower muscle strength results 21 . The Authors concluded that smoking may be negatively associated with the individual's overall muscle strength 22 .…”
Section: Discussionmentioning
confidence: 99%
“…However, this group showed a prevalence of RC tears in the right shoulder, which may have contributed to this result. In their review article, Abate et al 21 found that loss of muscle mass and muscle strength is related to the individual's age and is significantly influenced by cigarette smoking 21 . Musculoskeletal damage induced by cigarette smoking is due to impaired muscle metabolism, increased inflammation, and oxidative stress 20 .…”
Section: Discussionmentioning
confidence: 99%
“…second job (20+ hours per month) potential vibration exposure, categorized as low (car, van, bus, or coach use), medium (train or motorcycle use), or high (use of rock crusher, concrete production machinery, tractor, loader, excavator, bulldozer, grader, scraper, dumper, other earth-moving machinery, road roller, mower (seated), or off-road forestry vehicle); spare time potential vibration exposure, categorized as low (car, van, bus, or coach use), medium (train or motorcycle use), or high (use of snowmobile, ATV, horseback riding, mountain biking, mower, or tractor); and cigarette smoking (never smoked, past smoker, some current smoking, and daily smoking). 30…”
Section: Kneesmentioning
confidence: 99%